STRATEGI PEMASARAN UNTUK MEMPERTAHANKAN MARKET LEADERSHIP - Sugino Gunawan (Business Management Journal, 2017)
The increasing construction projects of office buildings that look very significant in Indonesia especially in Jakarta have made office furniture industry become more interesting. This case certainly become a gold opportunity for office furniture companies such as “X”, but on the other hand, local companies also faced with bold competition from foreign countries, especially from China. “X” is one of the oldest player in office furniture industry and also a market leader in the industry. It’s also faced by a very tight competition both from local and abroad. It is very important for “X” to expand its market share. The purpose of this study is to analyze the suitable marketing mix strategy to obtain market leadership in furniture business.Keywords: furniture industry, market leader, market share, marketing mix strategy